Clinical and laboratory features of systemic sclerosis complicated with localized scleroderma. Issue 3 (13th January 2015) - Toki, Sayaka; Motegi, Sei‐ichiro; Yamada, Kazuya; Uchiyama, Akihiko; Kanai, Sahori; Yamanaka, Masayoshi; Ishikawa, Osamu
Abstract Localized scleroderma (LSc) primarily affects skin, whereas systemic sclerosis (SSc) affects skin and various internal organs. LSc and SSc are considered to be basically different diseases, and there is no transition between them. However, LSc and SSc have several common characteristics, including endothelial cell dysfunction, immune activation, and excess fibrosis of the skin, and there exist several SSc cases complicated with LSc during the course of SSc. Clinical and laboratory characteristics of SSc patients with LSc remain unclear. We investigated the clinical and laboratory features of 8 SSc patients with LSc among 220 SSc patients (3.6%). The types of LSc included plaque (5/8), guttate (2/8), and linear type (1/8). All cases were diagnosed as having SSc within 5 years before or after the appearance of LSc. In three cases of SSc with LSc (37.5%), LSc skin lesions preceded clinical symptoms of SSc. Young age, negative antinuclear antibody, and positive anti‐RNA polymerase III antibody were significantly prevalent in SSc patients with LSc. The positivity of anticentromere antibody tended to be prevalent in SSc patients without LSc. No significant difference in the frequency of complications, such as interstitial lung disease, reflux esophagitis, and pulmonary artery hypertension, was observed. The awareness of these characteristic of SSc with LSc are essential to establish an early diagnosis and treatment.